Subungual exostosis in an 8-year-old child: clinical and dermoscopic description - Vincenzo Piccolo; Teresa Russo; Laís Leonor de Rezende; Giuseppe Argenziano (Sociedade Brasileira de Dermatologia, 2019)
Abstract We report the case of an 8-year-old child with subungual exostosis, whose diagnosis was suspected on the basis of dermoscopic findings and subsequently confirmed by X-ray and histopathology.